Polar Auxin Transport Determines Adventitious Root Emergence and Growth in Rice - Lin, Chen; Sauter, Margret (Frontiers in Plant Science, 2019)
Flooding is a severe limitation for crop production worldwide. Unlike other crop plants, rice (Oryza sativa L.) is well adapted to partial submergence rendering it a suitable crop plant to understand flooding tolerance. Formation of adventitious roots (ARs), that support or replace the main root system, is a characteristic response to flooding. In rice, AR emergence is induced by ethylene and in the dark where roots grow upward. We used the synthetic auxins 2,4-D and α-NAA, and the auxin transport inhibitor NPA to study emergence, growth rate and growth angle of adventitious roots. While α-NAA had no effect, NPA and 2,4-D reduced the root elongation rate and the angle with a stronger effect on root angle in the dark than in the light. Furthermore, NPA delayed emergence of AR primordia suggesting that efflux carrier-mediated auxin transport is required for all aspects of directed AR growth. Expression analysis using OsPIN:GUS reporter lines revealed that OsPIN1b and OsPIN1c promoters were active in the stele and root cap in accord with their predicted role in acropetal auxin transport. OsPIN2 was expressed at the root tip and was reduced in the presence of NPA. Auxin activity, detected with DR5:VENUS, increased in primordia following growth induction. By contrast, auxin activity was high in epidermal cells above primordia and declined following growth induction suggesting that auxin levels are antagonistically regulated in AR primordia and in epidermal cells above AR primordia suggesting that auxin signaling contributes to the coordinated processes of epidermal cell death and AR emergence.